Experimental Study of the Carbon Deposition from CH4 onto the Ni/YSZ Anode of SOFCs. Issue 2 (14th March 2016) - Fan, P.; Zhang, X.; Hua, D.; Li, G.
Abstract: A challenge in the operation of solid oxide fuel cells (SOFCs) with hydrocarbon fuels is the carbon deposition on the nickel/yttria‐stabilized zirconia (Ni/YSZ) anode. The Grabke‐type kinetic model has been proposed for the carbon formation based upon the assumption of elementary steps, which consist of a rate‐limiting dissociative chemisorption step and a stepwise dehydrogenation of the chemisorbed methyl group. This work experimentally studied the carbon formation on a SOFC Ni/YSZ anode exposed to CH4 +H2 gas mixtures. Experiments were conducted with various gas compositions of CH4 /H2 and temperatures in the range from 873 K to 1, 123 K. The experimental results were used to determine a kinetic model that was applied to the SOFC operating environments. Based on the experimental data, the formula for the carbon formation rate that is dependent on the operating temperature and the gas compositions of CH4 /H2 was established.